The Effect of Net Propit Margin and Debt to Asset Ratio To Stok Price and Earning Per Share as Intervening Variable (BUMN Companies Lq45 Period 2014-2018) - Diana Riyana Harjayanti; Hening Isdanti (Jurnal SEKURITAS (Saham, Ekonomi, Keuangan dan Investasi), 2021)
Purpose of the research to examineeffect of variable Net Profit Margin (NPM), Debt to Asset Ratio (DAR),andEarningPerShare (EPS) as intervening variable effect onthe stockpricesofBUMN company (State-Owned Companies) included inthe LQ45index on Indonesian Stock Exchange with period2014-2018.Thepopulationinthisresearchare BUMN company (state-owned companies)thatregisteredLQ45indexontheIndonesiaStockExchangein2014to 2018. Based on the results of the panel data model selection test using the Chow test, Langrage Multiplier, Hausman, the conclusion is the Fixed Effect panel data model. Results F test, both Net Profit Margin (NPM), Debt to Asset Ratio (DAR) simultaneously effect to Earning per Share (EPS) and Stock Price (HS). Other result from F test, Net Profit Margin (NPM), Debt to Asset Ratio (DAR), Earning per Share (EPS) simultaneously effect to Stock Price (HS). Earning Per Share as intervening variable does not mediate independent variable Net Profit Margin (NPM) and Debt to Asset Ratio (DAR) to dependent variable  Share Prices (SP).